2002
DOI: 10.1121/1.1490594
|View full text |Cite
|
Sign up to set email alerts
|

Buildup and breakdown of echo suppression for stimuli presented over headphones—the effects of interaural time and level differences

Abstract: The current study investigates buildup and breakdown of echo suppression for stimuli presented over headphones. The stimuli consisted of pairs of 120-micros clicks. The leading click (lead) and the lagging click (lag) in each pair were lateralized on opposite sides of the midline by means of interaural level differences (ILDs) of +/-10 dB or interaural time differences (ITDs) of +/-300 micros. Echo threshold was measured with an adaptive one-interval, two-alternative, forced-choice procedure with a subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 29 publications
(21 reference statements)
6
28
0
Order By: Relevance
“…Brown and Stecker, 2010;Stecker and Brown, 2010 . This result suggests that the mechanism of jitter-reduced onset weighting may be separate from the mechanism facilitating greater cue-averaging for ILD, an interpretation consistent with similar time courses of ITD and ILD sensitivity evidenced in some paradigms (e.g., studies of binaural adaptation, and different time courses of sensitivity evidenced in others (e.g., studies of the precedence effect, Krumbholz and Nobbe, 2002;Saberi et al, 2004;cf. Stecker and Brown, 2010).…”
Section: B Greater Cue-averaging For Ild Than Itdsupporting
confidence: 48%
See 2 more Smart Citations
“…Brown and Stecker, 2010;Stecker and Brown, 2010 . This result suggests that the mechanism of jitter-reduced onset weighting may be separate from the mechanism facilitating greater cue-averaging for ILD, an interpretation consistent with similar time courses of ITD and ILD sensitivity evidenced in some paradigms (e.g., studies of binaural adaptation, and different time courses of sensitivity evidenced in others (e.g., studies of the precedence effect, Krumbholz and Nobbe, 2002;Saberi et al, 2004;cf. Stecker and Brown, 2010).…”
Section: B Greater Cue-averaging For Ild Than Itdsupporting
confidence: 48%
“…Additionally, TWFs for lateralization suggest that onset dominance is reduced for ILD relative to ITD in both bilateral CI users (van Hoesel, 2008a,b) and normal-hearing listeners . Suggestive of further differences in the time courses of ITD and ILD processing, Krumbholz and Nobbe (2002) demonstrated a striking disparity between ITD-and ILD-based "echo thresholds" in the buildup and breakdown of the precedence effect, with buildup more robust for click pairs carrying ITD than ILD and breakdown much more robust for click pairs carrying ILD than ITD. In the present investigation (and the previous, Brown and Stecker, 2010) we have operationally defined onset dominance as the salience of onset information over longterm average information (AUC 1 À AUC mean ) after Saberi and Perrott (1995).…”
Section: B Greater Cue-averaging For Ild Than Itdmentioning
confidence: 99%
See 1 more Smart Citation
“…Keen and Freyman, 2009) for stimuli presented in the free field. Krumbholz and Nobbe (2002) demonstrated such breakdown to also occur during headphone presentation but only when the stimuli were lateralized by ILD and not when lateralized by ITD alone. That result is generally consistent with the maintained sensitivity to post-onset ILD demonstrated in the current study.…”
Section: Limited Rate-dependence Of These Effectsmentioning
confidence: 99%
“…It has been suggested that the strength of the perceptual suppression of echoes ͑''precedence effect''͒ varies with the spatial separation between the primary sound and the reflections ͑Litovsky et al, 1999; see also Shinn-Cunningham et al, 1993;Krumbholz and Nobbe, 2002͒. In Zurek's dichotic condition, the primary sound and the reflection had different ITDs ͑0 and 500 s͒, so, when sounded separately, they would be perceived in different lateral positions, and it may be that the salience of coloration decreases with increasing lateral displacement between primary sound and reflection.…”
Section: Introductionmentioning
confidence: 98%